Old model organisms and new behavioral end-points: Swimming alteration as an ecotoxicological response. (July 2017) - Faimali, Marco; Gambardella, Chiara; Costa, Elisa; Piazza, Veronica; Morgana, Silvia; Estévez-Calvar, Noelia; Garaventa, Francesca
Abstract: Behavioral responses of aquatic organisms have received much less attention than developmental or reproductive ones due to the scarce presence of user-friendly tools for their acquisition. The technological development of data acquisition systems for quantifying behavior in the aquatic environment and the increase of studies on the understanding the relationship between the behavior of aquatic organisms and the physiological/ecological activities have generated renewed interest in using behavioral responses also in marine ecotoxicology. Recent reviews on freshwater environment show that behavioral end-points are comparatively fast and sensitive, and warrant further attention as tools for assessing the toxicological effects of environmental contaminants. In this mini-review, we perform a systematic analysis of the most recent works that have used marine invertebrate swimming alteration as behavioral end-point in ecotoxicological studies by assessing the differences between behavioral and acute responses in a wide range of species, in order to compare their sensitivity. Highlights: Behavioral responses of aquatic organisms are used for environmental monitoring. Swimming behavior of marine invertebrates as ecotoxicological end-point is discussed. We analyze different analysis systems for assessing swimming performance. The sensitivity of swimming alteration is compared to mortality and immobility. Swimming behavior is a suitable end-point to evaluate marine environmental status.